Representations and Concepts of Borders in Digital Strategy Games and Their Potential for Political Education in Geography Teaching - Sebastian Seidel; Patrick Bettinger; Alexandra Budke (MDPI AG, 2019)
In Germany, 93% of young people between the ages of 10 and 18 play video games daily. Political geography, in particular popular geopolitics, have found that video games can help to establish and develop people's understanding of geopolitics. Consequently, this affects geography education, providing both challenges and opportunities for teaching. Geography teaching is an integral part of political education as students need to understand how boundaries and territories create spaces with regards to social power and become the object of political conflict. Reflection plays a central role in understanding and deconstructing such spatial constructions. In this article, we examine representations and concepts of borders in digital strategy games and the perception and reflection of these by the players. The results provide an outlook on the potential and the challenges of digital strategy games for political education in geography lessons in secondary schools as well as for teacher training at universities. For this reason, possible approaches for education and training will be outlined on the basis of the results.